PENGEMBANGAN MEDIA PEMBELAJARAN BERBASIS VIDEO CONTENT YOUTUBE PADA MATA KULIAH SEJARAH MUSIK MATERI PERKEMBANGAN MUSIK KUNO - Mifta Firdhani, Aldhila (Program Studi Pendidikan Musik, 2024)
The objectives of this study were (1) to develop learning media based on YouTube video content in the Music History course, material on the history of ancient music, (2) to test the feasibility of learning media based on YouTube video content in the History of Music course on the history of ancient music, and (3) to find out increased student interest in learning after using this learning medium as an additional source of information for students of music education study programs to understand the history of ancient music. This research and development stage includes needs analysis, planning, development, and testing of use. The assessment and product feasibility test in this alpha test involved 2 (one) media experts. The product trial (beta test) involved 32 students as test subjects. The data in this research and development were collected through questionnaires and interest in learning tests. The data analysis technique used is descriptive qualitative technique, quantitative descriptive, and different test. The results of the research and development indicated that: (1) the feasibility of learning media based on YouTube video content based on the media expert's assessment reached a score of 5.64 with the criteria of